Does increasing parents' schooling raise the schooling of the next generation? Evidence based on conditional second moments - Lídia Farré; Roger Klein; Francis Vella (Institute for the Study of Labor (IZA), 2009)
This paper investigates the degree of intergenerational transmission of education for individuals from the National Longitudinal Survey of Youth 1979. Rather than identifying the causal effect of parental education via instrumental variables we exploit the feature of the transmission mechanism responsible for its endogeneity. More explicitly, we assume the intergenerational transfer of unobserved ability is invariant to the economic environment. This, combined with the heteroskedasticity resulting from the interaction of unobserved ability with socioeconomic factors, identifies this causal effect. We conclude the observed intergenerational educational correlation reflects both a causal parental educational effect and a transfer of unobserved ability.
urn:nbn:de:101:1-2009021065
Keywords: C31; J62; 330; Intergenerational mobility; endogeneity; conditional correlation; Bildungsniveau; Eltern; Kinder; Generationenbeziehungen; Momentenmethode; Schätzung; USA